2011
DOI: 10.1007/s12032-011-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation in multiple myeloma and lymphoma: an analysis of factors influencing stem cell collection and hematological recovery

Abstract: Autologous stem cell transplantation is standard treatment for newly diagnosed younger patients with multiple myeloma and for relapsed or refractory Hodgkin or non-Hodgkin lymphoma. Patient characteristics influencing the yield from stem cell collection and time from transplant to platelet recovery were retrospectively analyzed in 630 consecutive patients, attempting to define adequate amounts of CD34+ cells to collect and reinfuse; 509/630 patients (81%) mobilized the requested CD34+ cell number. Factors infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…These outcomes are probably partly due to patients’ intrinsic bone-marrow function. We have previously shown that the average number of harvest days to obtain 5 million cells/kg was between 1.4 and 1.8 in all age groups, and that 19% did not reach the target, but 65% of these still proceeded to ASCT [25]. Today, with plerixafor, fewer patients do not reach the 5 million target, and, after a careful assessment of pros and cons, we do transplant the relatively few patients who have a yield of 2–5 million/kg.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are probably partly due to patients’ intrinsic bone-marrow function. We have previously shown that the average number of harvest days to obtain 5 million cells/kg was between 1.4 and 1.8 in all age groups, and that 19% did not reach the target, but 65% of these still proceeded to ASCT [25]. Today, with plerixafor, fewer patients do not reach the 5 million target, and, after a careful assessment of pros and cons, we do transplant the relatively few patients who have a yield of 2–5 million/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Fast recovery of platelets to greater than 50 x 10 9 /l within 14 days after high-dose cyclophosphamide and < or = 12 months of prior chemotherapy were the best predictors of early engraftment [29]. Yuan S et al [30] investigated the post- transplant outcomes of 105 adult patients with lymphoma and compared the post-transplant outcomes of 21 patients who received Plerixafor in addition to G-CSF ± chemotherapy, because of poor mobilisation, with those of 84 patients who mobilised well without Plerixafor. Despite collecting significantly lower CD34+ cell doses (median of 3.41 vs. 6.05×10 6 /kg, p < 0.0001) than control patients and requiring more collection days, Plerixafor-mobilized patients showed comparable early engraftment characteristics except for slightly delayed neutrophil engraftment (median 11 vs. 10 days, p = 0.002) and lower median neutrophil counts (2.1 vs. 2.6 × 10 9 /l, p = 0.04) at one month after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies carried out to investigate this question showed that the diagnosis of lymphoma, [14][15][16][17][18][19] thrombocytopenia, 14,[20][21][22][23] older age [18][19][20][21][23][24][25] and polytreatment 14,16,19,25,26 , among other factors, emerged as the main potential factors for the prediction of poor recruitment of hematopoietic stem cells.…”
Section: Predictive Factors Of Poor Mobilizationmentioning
confidence: 99%